2014
DOI: 10.4161/19490992.2014.965111
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic polyamines: new compounds specific to actin dynamics for mammalian cell and fission yeast

Abstract: Actin is a major actor in the determination of cell shape. On the one hand, site-directed assembly/disassembly cycles of actin filaments drive protrusive force leading to lamellipodia and filopodia dynamics. Force produced by actin similarly contributes in membrane scission in endocytosis or Golgi remodeling. On the other hand, cellular processes like adhesion, immune synapse, cortex dynamics or cytokinesis are achieved by combining acto-myosin contractility and actin assembly in a complex and not fully unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Polyamine is required during cell migration for forming lamellipodia, stress fibers, and integrin subunit a1. It also increases the K+ channel mediated Ca 2+ influx and aids FAK in inducing paxillin phosphorylation [32,[39][40][41][42]. Targeted inhibition of ODC was correlated with abnormal morphology of actin-cytoskeleton of metastatic cells during migration.…”
Section: The Effects Of Arginine Deprivation On Cell Migration and In...mentioning
confidence: 97%
“…Polyamine is required during cell migration for forming lamellipodia, stress fibers, and integrin subunit a1. It also increases the K+ channel mediated Ca 2+ influx and aids FAK in inducing paxillin phosphorylation [32,[39][40][41][42]. Targeted inhibition of ODC was correlated with abnormal morphology of actin-cytoskeleton of metastatic cells during migration.…”
Section: The Effects Of Arginine Deprivation On Cell Migration and In...mentioning
confidence: 97%
“…To become active, WAVE2 is phosphorylated at tyrosine 150 within the WAVE regulatory complex, which leads to release of its VCA domain, which in turn binds to and activates the Arp2/3 complex that nucleates and polymerizes actin at branching points ( Leng et al, 2005 ; Mendoza, 2013 ). To assess whether alterations in actin dynamics caused the functional impairment of the Rac1 −/− CD cells, we treated them with the synthetic polyamine C8N6-BPA, which reduces the turnover of actin and enhances nucleation of actin at the cell edge to generate lamellipodia ( Nedeva et al, 2013 ; Riveline et al, 2014 ). C8N6-BPA increased the number of cells with lamellipodia and spreading area in Rac1 /f/ , but not Rac1 −/− , CD cells, indicating a defect of actin nucleation and branching ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Also, many naturally occurring drugs like latrunculin A and B, cytochalasin D, jasplakinolide, and phalloidin, can bind to actin and alter actin filament dynamics. 10,11 A vast number of literature reports have shown that actin polymerization can be promoted in the presence of positively charged (surfaces) molecules like polyamines, 12 cationic liposomes, 13 positively charged lipids, 14 and peptides 15 via possible non-specific electrostatic binding. 16,17 However, the practical relevance of most of the synthetic substrates is limited due to their high measure of toxicity; thus, new designs and synthesis of actin-interacting materials with low toxicity are of tremendous bio-importance such as in nucleocytoplasmic transport, and wound healing.…”
Section: Introductionmentioning
confidence: 99%